2018
DOI: 10.1002/anie.201804702
|View full text |Cite
|
Sign up to set email alerts
|

Ionothermal Synthesis of Triazine–Heptazine‐Based Copolymers with Apparent Quantum Yields of 60 % at 420 nm for Solar Hydrogen Production from “Sea Water”

Abstract: Polymeric carbon nitride (PCN), in either triazine or heptazine form, has been regarded as a promising metal-free, environmentally benign, and sustainable photocatalyst for solar hydrogen production. However, PCN in most cases only exhibits moderate activity owing to its inherent properties, such as rapid charge carrier recombination. Herein we present a triazine-heptazine copolymer synthesized by simple post-calcination of PCN in eutectic salts, that is, NaCl/KCl, to modulate the polymerization process and op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
304
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 426 publications
(313 citation statements)
references
References 54 publications
(129 reference statements)
8
304
0
1
Order By: Relevance
“…Furthermore, high‐resolution transmission electron microscopy (HR‐TEM, Figure B) was employed to examine Pt distribution on C 3 N 4 nanorods. The inset HR‐TEM image shows a lattice spacing of 0.94 nm, corresponding to the (100) plane of an in‐planar arrangement of nitrogen‐linked heptazine units . Specifically, no obvious Pt particle or cluster was observed, thus suggesting highly uniform Pt loading on the C 3 N 4 .…”
Section: Figurementioning
confidence: 98%
“…Furthermore, high‐resolution transmission electron microscopy (HR‐TEM, Figure B) was employed to examine Pt distribution on C 3 N 4 nanorods. The inset HR‐TEM image shows a lattice spacing of 0.94 nm, corresponding to the (100) plane of an in‐planar arrangement of nitrogen‐linked heptazine units . Specifically, no obvious Pt particle or cluster was observed, thus suggesting highly uniform Pt loading on the C 3 N 4 .…”
Section: Figurementioning
confidence: 98%
“…Particularly, copolymerization with monomers is an effective way to tailor the structure and properties of carbon nitride at molecular scale , . The copolymerization strategy can always generate more grain boundary defects and improve the crystallinity of carbon nitride, which is beneficial to promote the separation and fast transfer of photogenerated carriers compared to amorphous counterparts , . Nevertheless, the photocatalytic activity and selectivity of g‐C 3 N 4 is still unsatisfactory for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, DA−HM1 showed significantly enhanced photocatalytic activity because of extended spectral absorption and high efficiency in charge separation and photoexcited carrier transfer. Very recently, they have also reported triazine−heptazine copolymers synthesized through simple post calcination of polymeric carbon nitride (PCN) in eutectic salts (NaCl/KCl) to accelerate the polymerization process and tailored the structures, morphologies, and electronic and optical properties of the materials . It was confirmed that these D‐A heterostructures significantly accelerate interface CT and thus enhance photocatalytic activity (CN−NaK, AQY=60 % at 420 nm).…”
Section: Photocatalysts Based On Triazine Frameworkmentioning
confidence: 93%